Laboratory fatigue evaluation of modified and unmodified asphalt binders in Stone Mastic Asphalt mixtures using a newly developed crack meander technique - Muniandy, Ratnasamy; Che Md Akhir, Nor Azurah; Hassim, Salihudin; Moazami, Danial (Elsevier, 2014)
This paper looks into the fatigue evaluation of modified and unmodified asphalt binders in Stone Mastic Asphalt (SMA) mixtures using a Crack Meander (CM) technique. Specimens images were taken during the repeated load indirect tensile fatigue test (ITFT) and crack initiation, propagation and failure were analyzed using a developed “Measurement and Mapping of Crack Meander” (MMCM) Software. The results of crack analysis on every SMA specimens were compared with tensile strain plots obtained from the ITFT test. It was concluded that, in addition to strain or dynamic modulus plots, fatigue behavior can be determined using crack appearance as an alternative method.